If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -2x) = -11(x + -2) (1 * 5 + -2x * 5) = -11(x + -2) (5 + -10x) = -11(x + -2) Reorder the terms: 5 + -10x = -11(-2 + x) 5 + -10x = (-2 * -11 + x * -11) 5 + -10x = (22 + -11x) Solving 5 + -10x = 22 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. 5 + -10x + 11x = 22 + -11x + 11x Combine like terms: -10x + 11x = 1x 5 + 1x = 22 + -11x + 11x Combine like terms: -11x + 11x = 0 5 + 1x = 22 + 0 5 + 1x = 22 Add '-5' to each side of the equation. 5 + -5 + 1x = 22 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 22 + -5 1x = 22 + -5 Combine like terms: 22 + -5 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| 10b=2b-16 | | -5c=5/24 | | 3x-6=3-6x | | 8b=5b-9 | | 2/3+4/15 | | -2(n-8)=-4(-1-n) | | -7x-4y=28/-4 | | x-(-2/3)=2/3 | | 6-7x=-5x-2 | | 6xa=5 | | x/4.4=-15.6 | | 10x=5/12 | | 2x+1/5x+3 | | 3(2b+6a)=4b-8 | | 9(42-3)=9x+15 | | 2x=8y+24 | | x/4+3 | | 6x+2=3x-34 | | t/6.8=-0.2 | | 9b=2b+7 | | g/3+15=26 | | 10-x=5x+10 | | 6/11w=-1/5 | | 10=5/3/4 | | 3/2=n+2 | | 4x-8=8(1+x) | | (-3i+4j-5k)*(3i-4j+5k)= | | -18x+8y=3 | | -2=2x^2-12x | | 6-20x+12(x^2)=0 | | 5x-7/x-2-2x-1/x-2 | | .8(9+2x)=40 |